Endoprosthesis replacement of the thoracic aorta for traumatic dissection and pseudoaneurysm - A. N. Vachev; D. A. Chernovalov; A. M. Frantcevich (Вестник хирургии имени И.И. Грекова)
Aortic injury in closed chest trauma takes the second place in the structure of mortality in closed injuries. The type of aortic injury is a crucial factor in determining the optimal timing of the operation. For many years, the treatment strategy was reduced to immediate surgical intervention. The mortality rate in open operations is still high. The widespread introduction of endovascular technologies and aortic endoprosthetics has significantly reduced mortality and reduced the number of severe postoperative complications. With the advent of new endoprostheses, the possibilities of treatment have increased even more and its results have improved for various aortic injuries. A case of successful treatment of a patient with traumatic dissection and pseudoaneurysm of the thoracic aorta by endoprosthetics is presented.